Skin Shrinkage with Vibration Amplification of Sound Energy at Resonance (VASER) Liposelection of Abdomen: Avoiding Abdominoplasty - Alam, Dr Munir (International Journal of Innovative Research in Medical Science, 2020)
Objective / Purpose of the Study: For abdominal reshaping / contouring, patient with excess abdominal skin and redundant fat quite often require abdominoplasty / tummy tuck. Inconsistent results achieved with traditional liposuction especially in the supraumbilical area. This study is to assess the role of abdominal VASER liposelection and if the abdominoplasty can be avoided. Material and Methods: This is retrospective cross sectional observational study conducted at Dundrum Medical Cosmetic Clinic, Dublin 16, Ireland. The study period includes two years from March 2009 to February 2011. In this study total number of consecutive 85 patients, operated by single surgeon were included with type I-IV patient category according to Matarasso classification system (1). There were 10 (11.8%) male and 75 (88.2%) female patient with mean age 42.4 years ± 10.95 years. Results: All of the 85 patients were treated with abdominal VASER liposelection. There were 75 female (88.2%) patients and 10 male (11.8%) patients in this study. Seven (8.2%) female patient require second session of VASER liposelection procedure 3 months after the first procedure and 3 (3.5%) female patient underwent third session to complete the abdominal contouring. None of the total 10 male patient required 2nd or 3rd session of abdominal VASER liposelection. The satisfaction level achieved 90 to 100 % by using visual analogue scoring system for all types I - IV abdomen. No early or late complication was noted in this study. Conclusion: This is a low risk, minimally invasive, scarless ambulatory technique performed under local anaesthetic, highly satisfactory to the patient as well as surgeon and is effective in all the categories of protuberant abdomen avoiding the local and systemic risk of abdominoplasty.